2017
DOI: 10.18632/oncotarget.17619
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes of invasive urothelial carcinoma cells are characterized by a specific miRNA expression signature

Abstract: Muscle-invasive bladder cancer (MIBC) represents a highly aggressive tumor type compared to non-muscle-invasive tumors. MIBC is characterized by specific molecular alterations, which may also modulate extracellular tumorigenic effects. Tumor-associated exosomes, especially exosomal miRNAs, are important regulators in the interaction between tumor cells and tumor microenvironment by affecting tumor-promoting processes in target cells. It is important to analyze whether their exosomal patterns also reflect the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…In a study by Baumgart et al, a panel of miRNAs (miR-141-3p, miR-200a-3p, miR-200b-3p, miR-200c-3p, miR-205-5p, miR-224-5p, and miR-429-3p) was found to be downregulated in exosomes of invasive BC cells (T24, J82, and 253J-BV) compared to noninvasive BC cells (RT112; 5637), while miR-99a-5p and miR-137-3p were increasingly expressed in invasive BC cells. 39 Additionally, the authors found that miR-141-3p, miR-200a-3p and miR-205-5p were significantly downregulated, while miR-99a-5p was upregulated in urinary exosomes of MIBC patients compared to those in their NMIBC counterparts. 39 miR-375-3p (once named miR-375) is a tumor-related miRNA located at Chr2 (219 001 648-219 001 669), 40 which has been discovered to be commonly dysregulated in multiple human cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Baumgart et al, a panel of miRNAs (miR-141-3p, miR-200a-3p, miR-200b-3p, miR-200c-3p, miR-205-5p, miR-224-5p, and miR-429-3p) was found to be downregulated in exosomes of invasive BC cells (T24, J82, and 253J-BV) compared to noninvasive BC cells (RT112; 5637), while miR-99a-5p and miR-137-3p were increasingly expressed in invasive BC cells. 39 Additionally, the authors found that miR-141-3p, miR-200a-3p and miR-205-5p were significantly downregulated, while miR-99a-5p was upregulated in urinary exosomes of MIBC patients compared to those in their NMIBC counterparts. 39 miR-375-3p (once named miR-375) is a tumor-related miRNA located at Chr2 (219 001 648-219 001 669), 40 which has been discovered to be commonly dysregulated in multiple human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…39 Additionally, the authors found that miR-141-3p, miR-200a-3p and miR-205-5p were significantly downregulated, while miR-99a-5p was upregulated in urinary exosomes of MIBC patients compared to those in their NMIBC counterparts. 39 miR-375-3p (once named miR-375) is a tumor-related miRNA located at Chr2 (219 001 648-219 001 669), 40 which has been discovered to be commonly dysregulated in multiple human cancers. In most cases, such as gastric carcinoma tissue and cells, 41 hepatocellular carcinoma, 42 colorectal carcinoma, 43 esophageal squamous cell carcinoma, 44 and salivary gland cancers, 45 miR-375-3p was downregulated in tumors compared to normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Other published results (118) suggest that exosome-mediated discharge of tumor-suppressor miRNA is selected in tumor evolution as a mechanism to organize the activation of a metastatic cascade (119). The load of exosomes is given for the parental cells and the circumstances in which they deliver them, which implies that circulating miRNAs in exosomes have the ability to serve as prognostic and predictive biomarkers (120).…”
Section: Exosomes Secreted From Mscs Have a Totally Different Effect mentioning
confidence: 99%
“…Furthermore, based on their stability in body fluids, especially exosomal miRNAs are discussed to be useful diagnostic and prognostic biomarkers in liquid biopsies. Baumgart and colleagues showed that exosomes from invasive BC cell lines, compared to non-invasive BC cell lines, are characterized by a specific miRNA signature which could play a role in the modification of the tumour microenvironment ( p < 0.05; FC > 1.5) [ 236 ]. These results confirmed the hypothesis that the molecular content of exosomes is, at least in part, similar to that of host cells and reflects their cellular properties.…”
Section: Liquid Biopsy Biomarkers and Their Clinical Applicationsmentioning
confidence: 99%
“…These results confirmed the hypothesis that the molecular content of exosomes is, at least in part, similar to that of host cells and reflects their cellular properties. However, Baumgart also analysed urinary exosomes from BC patients and they exhibited only in part the miRNA alterations detected in cell line exosomes [ 236 ]. Therefore, further analyses will have to clarify the functional relevance of exosomal miRNAs and their role as molecular markers in liquid biopsies.…”
Section: Liquid Biopsy Biomarkers and Their Clinical Applicationsmentioning
confidence: 99%